Beyond SERVQUAL: A paradigm shift - Al-Allak B.A.; Bekhet H.A. (2023)
The current exploratory study reviews the most widely used service quality models such as SERVQUAL, SERVPERF, and the Human-Societal Element (HSE) model, and presents a critique of each of them by relying on various empirical studies that have proven beyond any doubt the inability of such models to ensure the proper measurement of service quality in various and/ or specific service settings. It is evident that the orthodox SURVQUAL model is fraught with numerous shortcomings and operational flaws, major among them is its inapplicability to all cases, countries, services, ethnicities, etc. Modified service quality models have been developed in an attempt to fill the deficiency gaps of the SERVQUAL model. Yet these modified models have also fallen short of reflecting the real service quality dimensions impacting customer's satisfaction. The current study suggests a number of solutions that may lead to the development of a model/ models that enjoy a certain degree of consistency and universality. The implications of such developments are highlighted, and suggestions for future research are presented. Light is also shed on the limitations of the current study.